Selected Natural and Synthetic Phenolic Compounds with Antileishmanial Activity: A Five-year Review - Rojas de Arias, Antonieta; Pandolfi, Enrique; Celeste Vega, Maria; Rolon, Miriam (Current Bioactive Compounds, 2012)
Leishmaniasis is among the neglected diseases that represent 90% of the world burden of morbidity. According to the WHO, there are 12 million people, mostly deeply impoverished who suffer from visceral leishmaniasis (VL). The drugs currently used for the treatment of human cutaneous and visceral leishmaniasis are toxic, have severe adverse reactions which limit their use, and have presented teratogenic and cardiotoxic effects and increasing resistance. Given this scenario, the search for new, accessible and effective drugs for the treatment of leishmaniasis is a priority. This review aims to provide an overview of selected phenolic compounds with antileishmanial activities that have been published from 2007 to the present. Natural source or efficient synthesis, biological assays and possible mechanisms of actions are also described. Five flavonoids, six chalcones and three polyphenols have shown a selective index (SI) equal or greater than 20 which places them with greater antileishmanial activity. Quercitrin (3), hispidulin (6), octa-acetylhyperoside (11a), biochanin A (13) and ageconyflavone C (14) showed a SI range between 19.5 and 100. Chalcones 31, 33, 41, 42 65 and 67 were the highest antileishmanial compounds. Polyphenols 74 and 85 showed an important selective index when tested on promastigotes (71.4) and amastigotes (36.5) of L major and axenic amastigotes of L. mexicana (20). Compound 83 has demonstrated a potent in vitro (19.7) and in vivo effect on Balb/c mice experimentally infected with L. amazonensis. A wide range of biological assays with several strains and different parasite forms, have identified promising compounds, but few of them are conducted to clinical trials. This restriction emphasizes the necessity to reach a consensus regarding in vitro and in vivo screening protocol to advance leading compounds to clinical trials.
Keywords: Leishmaniasis